Feminist Imaginaries of Equitable, Just Care: Our Pictures Speak Louder than Words - Ng, Lynn (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
Globally, not just in the case of Singapore, which is the focus of this paper, migrant care workers are a devalued and unappreciated workforce. Long before the pandemic, issues of migrant rights and care shortages were major topics of concern for feminist adult education and care work scholars, who advocate for the importance of critical hope and the transformative potential of imaginations. As human communication pivots online, physical face-to-face encounters dwindle while digital solidarities thrive. In this hybrid scenario, I narrate the structurally oppressive circumstances of live-in employment alongside an online (Facebook) support group that asserts its members’ rights to receive, not simply provide, care. For my migrant worker activist research participants, care and digital activism are mutually interactive social processes that challenge Singapore society’s dominant market mentality in the educational, learning, and socialization practices of family care. Power asymmetries often prevent migrant worker activists such as foreign “maids,” as they are often disparagingly called in the local parlance, from mobilizing their transformative feminist imaginations into policy change. Based on my findings, I call for a reciprocal approach to reconfiguring care ethics and practice that centres migrant perspectives. I invite colleagues to join me in storytelling about resilient groups and individuals who embrace the imaginative power of critical hope to rewrite the status quo of public knowledge.